Kedudukan Peranan Notaris dalam Akad Murabahah di Bank Syariah - Noviani, Angy Indah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Basically, the existence of guarantees in sharia banking is a form of bank confidence in the ability of prospective customers who receive facilities to pay off and return the facilities they receive. The aim of this research is: To analyze legal certainty in the financing philosophy of Murabahah contracts in Sharia Banking. And to analyze the role of notaries in murabahah contracts in Sharia banks. Types of legal research are divided into 2 (two) types, namely Normative Legal research and Empirical Legal research. The type of research used by researchers in this research is researchBased on the results of the discussion, the position of Murabahah financing in Sharia Banks is the most popular among the public. Murabahah financing is a product that does not recognize usury or the interest system and murabahah products really help people to make their wishes come true. And the function of a notary is very important in the field of sharia banking, especially in making contracts to channel funds through financing to customers, specifically to create legal certainty in the legal relationship between sharia banks or sharia business units and their customers, namely by making contracts. The financing is in the form of an authentic deed based on the principles of freedom of contract and sharia principles.